Risk Factors for the Development of Hemophagocytic Lymphohistiocytosis in Children With Severe Adenovirus Pneumonia: A Single-Center Retrospective Study - Zhang, Hua-yong; Xiao, Min; Yan, Fan; Zhang, Mao-rong; Zhang, Yong (Frontiers in Pediatrics, 2021)
Objective: To investigate and analyze the relevant risk factors for hemophagocytic lymphohistiocytosis (HLH) in children with severe adenovirus pneumonia (SAP). Methods: A retrospective study of children with SAP was performed in 30 cases developing HLH and 94 cases not developing HLH from December 2018 to August 2019. The binary logistic regression analysis was used to identify risk factors that were significantly associated with the development of HLH after the univariate analysis, and the receiver operating characteristic (ROC) curve was performed to find out the cut-off value for the significant relevant factors. Results: Two factors were associated with the development of HLH, which were the length of fever (OR=1.331,95%CI:1.002-1.769) and triglycerides (TG) (OR=17.345,95%CI:1.358-221.538). The cut-off value of the length of fever was 12.5 days, and the cut-off value of TG was 3.02mmol/L. Conclusion: Children with SAP who had a duration of fever over 12.5 days and the TG level over 3.02mmol/L are more likely to develop HLH.